THE IMPACT OF FINANCIAL LITERACY, FINANCIAL TECHNOLOGY, AND INTELLECTUAL CAPITAL ON MICRO SMALL, MEDIUM ENTERPRISES (MSMES) PERFORMANCE IN MANADO - Poluan, Efrani; Tulung, Joy Elly; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2025)
This research examines the Impact of Financial Literacy, Financial Technology, and Intellectual Capital on the Performance of Micro, Small and Medium Enterprises (MSMEs) in Manado. MSMEs play an important role in economic development, especially in developing countries such as Indonesia. However, they face major challenges related to financial management, technology adoption, and understanding of business management. This research uses a quantitative approach, collecting data through a structured online questionnaire to 96 MSMEs actors in Manado. Adopting multiple regression analysis testing procedure, using IBM SPSS Version 29 to analyze the data. The findings show that the level of financial literacy, financial technology, and intellectual capital has a positive effect on the performance of MSMEs simultaneously for partial only financial technology has slightly no impact. The results emphasize the need for stakeholder intervention to improve financial literacy, encourage the adoption of financial technology, and leverage intellectual capital to foster sustainable growth and competitiveness among MSMEs. Keywords: Financial Literacy, Financial Literacy, Intellectual Capital, Micro Small Medium Enterprises (MSMES)